(untitled) (Hekima Review, 2016)
Infertility has increasingly brought challenges to many couples; prominent amongst them is childlessness. Most couples seem vulnerable to any procedure that could quench their thirst for children of their own. Available biomedical practices such as com mercialization of surrogate mothering and spare IVF embryos lack satisfactory solution to the challenges. Their inherent ethical dilemmas not only aggravate family tension but also confuse the faith of many Catholic couples. Hence, the article argues that the Church’s wisdom in the light of Donum Vitae offers reconciliation to these dilemmas. She teaches that “the human must be respected as a person created in the image and likeness of God who belongs to the moral community from the first moment of his existence (constituted in the zygote resulting from fertilization). Thus, commercializing surrogate mothering and spare IVF embryos as means of generating human life is absolutely immoral. It necessitates reappraisal of such a foundation.